THE EFFECT OF THE IMPLEMENTATION OF GREEN ACCOUNTING, ENVIRONMENTAL PERFORMANCE, INTELLECTUAL CAPITAL ON SUSTAINABLE GROWTH - Yustinne, Fulan; Widodo, Condro (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to examine and analyze the effect of green accounting, environmental performance, and intellectual capital on sustainable growth. The population used in this study consists of manufacturing companies listed on the IDX during 2020-2022 and received an environmental performance assessment from the Ministry of Environment and Forestry. The sampling technique in this study used purposive sampling with a total sample of 117 data from 39 manufacturing companies with different sub-sectors. Data analysis was done using the multiple panel data regression method through the Eviews 12 program. Environmental pollution cases occur as a result of the company's operational activities. Xingye Logam Indonesia (XLI) resulted in economic losses due to the decline of PT. XLI. Therefore, investors need instruments to know the company's performance, such as sustainable growth rate. A sustainable growth rate aims as a filter tool to sort out industries that can survive in a competitive market. This research shows that green accounting has a significant positive effect on sustainable growth. However, this study found that environmental performance and intellectual capital do not affect sustainable growth. This study's novelty is adding intellectual capital variables and expanding the observation period.